#### Answer

$(5g)(g^{2}+4)(g-1)$

#### Work Step by Step

After grouping :
$=(5g^{4}-5g^{3})+(20g^{2}-20g)$
$=5g^{3}(g-1)+20g(g-1)$
$=(5g^{3}+20g)(g-1)$
$=(5g)(g^{2}+4)(g-1)$

Published by
Prentice Hall

ISBN 10:
0133500403

ISBN 13:
978-0-13350-040-0

$(5g)(g^{2}+4)(g-1)$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.